If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 6x + y = 0 Combine like terms: -9x + 6x = -3x -3x + y = 0 Solving -3x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -3x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 -3x + 0 = 0 + -1y -3x = 0 + -1y Remove the zero: -3x = -1y Divide each side by '-3'. x = 0.3333333333y Simplifying x = 0.3333333333y
| 3x^2+3y^2-3x-3y-5=0 | | 0.6(x+80)+0.8x=97 | | b(a-7)+3(7-2)=0 | | -16-10.2g=-17.7g+16.85 | | -2x+14y=-18 | | 6x-27=4x-15 | | 5+4[(3r+s)-(3r-s)]= | | 15-2*4(6-3)= | | x+(3x)=200 | | k/2-7=37 | | x+(x+3)=200 | | 2x^9y^7+8x^7y^6+14xy= | | ax+3=-7 | | 3x+8/7+x+23/4=13 | | 9x-6=4x+12+12 | | 4-z=-4 | | 6x-44=3x-26 | | 15-2(x-3)=31 | | -8(n+7)=4(1+n) | | -21x+71=-14x+36 | | 14+3x=6x+-7 | | 5x-8x+5x= | | 2.8+10.5+9=x | | 3x+x+6=2x+16 | | 4x+8x=-4 | | 0.5b+4=150+1p | | -2.6+2a=12 | | 2(x-8)+9=2x+3 | | 6p-4=26 | | 13+6=x | | x-6/5+6/5=-x/2 | | 7x-2+8x= |